PENGARUH TERAPI AL-QUR’AN SURAT ASH-SHAFF (2-3) UNTUK MENINGKATKAN INTEGRITAS SISWA MELALUI BIMBINGAN KELOMPOK DI SMP NEGERI 13 PEKANBARU - Yoan Pratiwi; Putri Umari; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the differences in the integrity of students before and after being given Al-Qur'an therapy Letter Ash-Shaff (2-3) through group guidance, and knowing the effect of Al-Qur'an therapy Ash-Shaff Letter (2-3 ) to improve the integrity of students through group guidance. The study was conducted at Pekanbaru State Junior High School 13 on 7 subjects with a purposive sampling technique. The research design was pre-experiment with the one group pre-test post-test model. The data collection instrument used is an instrument consisting of integrity indicators. The results showed that there were differences in the level of integrity of students before and after being given therapy for Al-Qur'an Surat Ash-Shaff (2-3) through group guidance with a significance value of 0.018 <0.05. The students' interventions which were the subjects of the study were 7 students who were previously in the low category after being given the Al-Qur'an Letter Ash-Shaff therapy (2-3) through group guidance, mostly in the high category. In addition, based on the Spearman rank test, it is known that there is a significant effect of Al-Qur'an therapy Ash-Shaff Letter (2-3) through group guidance on student integrity which is equal to 55% while 45% is influenced by other factors from outside and in students. Key Words: Al-Shaff Al-Qur'an Therapy (2-3), Student Integrity, Group Guidance.